Programa Ecoforte e o fortalecimento das redes de agroecologia: Demandas e possibilidades - Jéssica Maiara Rodrigues Martins; Regina Helena Rosa Sambuichi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The Ecoforte Program was created under the National Policy on Agroecology and Organic Production (PNAPO) with the objective of strengthening agroecology networks in Brazil. This research sought to understand how the expectations and demands of civil society to support and strengthen agroecology networks in the territories were internalized in the first edition of the Ecoforte-Redes Program. Therefore, qualitative research was done, with documental analysis and semi-structured interviews with key actors. The results show that Ecoforte was able to cover a wide range of characteristics identified by civil society as relevant to the strengthening of networks, such as funding for mobilization activities and the dynamics of the networks, the prioritization of training and technical assistance activities and support for projects that value diversity, including representative entities of traditional peoples and communities, as well as groups of women and youth. In the opinion of the interviewees, the extension and continuity of the Program were considered fundamental, both for the strengthening of a greater number of networks and for the strengthening of PNAPO itself.
Keywords: Q15; Q18; 330; agroecology networks; agroecology; Ecoforte program; sustainable rural development